Strategi Branding Based Club Melalui Media Sosial Instagram: Studi Kasus Mengenai Strategi Branding Based Club Menggunakan Tema Internet Culture Melalui Media Sosial Instagram - Bintang Sania Putri; Endri Listiani (Bandung Conference Series: Communication Management, 2022)
Abstract. Strategy is defined as long-term planning designed to achieve goals and objectives, while branding is the process of using the power of a brand to provide products and services. Branding creates a psychological structure that helps consumers to organize their knowledge of products and services in a way that makes decisions that clearly provide value to the company in the process. Where the author finds indications of how the Based Club makes a branding strategy by connecting it with the theme it carries, so that the theme affects the strategy it implements. This research method is qualitative using a case study approach. Data collection techniques used are interview and observation techniques, documentation and literature related to the Based Club. The result of this research is that the branding strategy applied by the Based Club through Instagram social media is an adaptive, idealistic and differentiation brand. They made the strategy based on the theme they carried, namely internet culture. From the internet culture theme, Based Club produces an adaptive strategy to continue to be relevant to the times and young people as their target market, idealistically, the Based Club always packs internet issues with their own style, then differentiation aims to be different from competitors in the Class Based Club who are more competitive. delivered a lot of statements on the product and its campaign. Abstrak. Strategi diartikan sebagai perencanaan jangka panjang yang disusun untuk mencapai tujuan dan sasaran sedangkan branding adalah proses penggunaan kekuatan merek untuk menyediakan produk dan layanan. Branding menciptakan struktur psikologi yang menolong konsumen untuk mengatur pengetahuan mereka tentang produk dan layanan dengan cara pengambilan keputusan yang jelas memberikan nilai bagi perusahaan dalam prosesnya. Dimana penulis menemukan indikasi bagaimana Based Club membuat strategi branding dengan menghubungkannya dengan tema yang diusungnya, sehingga tema mempengaruhi strategi yang diterapkannya. Metode penelitian ini adalah kualitatif dengan menggunakan pendekatan studi kasus. Teknik pengumpulan data yang digunakan adalah teknik wawancara dan observasi, dokumentasi dan kepustakaan berhubungan dengan pihak Based Club. Hasil dari penelitian ini strategi branding yang diterapkan Based Club melalui media sosial Instagram adalah brand yang adaptif, idealis dan diferensiasi. Mereka membuat strategi tersebut berdasarkan tema yang diusungnya yaitu internet culture. Dari tema internet culture, Based Club menghasilkan strategi yang adaptif agar terus relevan dengan zaman dan anak muda sebagai target pasar mereka, idealis yaitu Based Club selalu mengemas isu internet dengan gaya mereka sendiri, lalu diferensiasi bertujuan agar memiliki perbedaan dengan kompetitor sekelas Based Club yang lebih banyak menyampaikan statement pada produk dan campaignnya.